2015
DOI: 10.4067/s0718-95162015005000017
|View full text |Cite
|
Sign up to set email alerts
|

PGPR mediated Zinc biofertilization of soil and its impact on growth and productivity of wheat

Abstract: Objectives: This study describes Zinc biofortification of wheat using a rhizospheric isolate, Pseudomonas fluorescens strain Psd.Methods: The strain was used as a bio-ionculant in soil deficient in zinc and the plant-growth promoting potential and biofortification was assessed using a number of physical and biochemical parameters. The enzymatic studies indicated towards the zinc supply mediated by the strain Result: This plant-growth-promoting strain, apart from the Zn accumulation potential, has the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 27 publications
2
26
0
2
Order By: Relevance
“…Morley et al [26] and Sirohi et al [4] have reported that production of H+ and organic acids seem to be the most significant mechanisms for heterotrophic metal solubilization although some contribution may also arise from excretion of other metabolites, siderophores and CO 2 from respiration, the significance of all these processes being variable and dependent on the organisms and the growth conditions. Karamushka et al [27] suggested that the proton translocating ATPase of the plasma membrane generates the electrochemical gradients that are required for the acquisition of nutrients by active efflux of protons into the external medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morley et al [26] and Sirohi et al [4] have reported that production of H+ and organic acids seem to be the most significant mechanisms for heterotrophic metal solubilization although some contribution may also arise from excretion of other metabolites, siderophores and CO 2 from respiration, the significance of all these processes being variable and dependent on the organisms and the growth conditions. Karamushka et al [27] suggested that the proton translocating ATPase of the plasma membrane generates the electrochemical gradients that are required for the acquisition of nutrients by active efflux of protons into the external medium.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes essential nutrients (or metal compounds) such as P and S are present in a microbial habitat only in insoluble form, so microorganisms have to solubilize such compounds before uptake in order to survive [4]. In addition to that, solubilization of insoluble salts by bacteria has many technological applications e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another applied solution is the use of composted organic wastes as soil amendments (Calleja-Cervantes et al, 2015). Organic fertilizers not only supply organic matter to the soil, they also help: (1) form soil aggregates (Yazdanpanah et al, 2016); (2) improve soil porosity, bulk density and water holding capacity (Burrell et al, 2016); (3) conserve and increase the microbial diversity (Dignam et al, 2016); (4) remediate heavy metal and polycyclic aromatic compounds in contaminated soils (Chen et al, 2015); and, (5) promote crop growth (Sirohi et al, 2015;Debiase et al, 2016). Microbes introduced with organic fertilizers may inhibit plant pathogens (Wu et al, 2015;Ling et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The ACC deaminase enzyme modulates the level of ethylene by hydrolyzing ACC in ammonia and α-ketobutyrate (Marques et al, 2010). Pseudomonas fluorescens strain Psd solubilizes inorganic zinc and produces nitrate reductase along with certain antioxidant enzymes such as glutathione reductase and peroxidase which eventually supports the growth of wheat (Sirohi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%